Teaching the spoken language - Brown, Gillian (Cambridge University Press, 1983)
Teaching the Spoken Language is about teaching the spoken language. It presents in a highly accessible form the results of the author's important research on teaching and assessing effective spoken communication. The authors examine the nature of spoken language and how it differs from written language both in form and purpose. A large part of it is concerned with principles and techniques for teaching spoken production and listening comprehension. An important chapter deals with how to assess spoken language. The principles and techniques described apply to the teaching of English as a foreign and second language, and are also highly relevant to the teaching of the mother tongue